2006
DOI: 10.1016/s1472-6483(10)61997-9
|View full text |Cite
|
Sign up to set email alerts
|

Comet assay of cumulus cells and spermatozoa DNA status, and the relationship to oocyte fertilization and embryo quality following ICSI

Abstract: It has been postulated that apoptosis may affect cumulus cell and sperm DNA integrity, and therefore influence the outcome of assisted reproductive techniques. This study investigates apoptotic levels in both cumulus cells and spermatozoa, and their relationship with fertilization and embryo quality after intracytoplasmic sperm injection (ICSI). The neutral comet assay was performed on cumulus cells and semen samples from 55 couples with male factor infertility undergoing ICSI treatment. Cells were fixed in ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…Before insemination, the percentage was 34.3 AE 3.7%. This result was higher than the 3.0% to 22.6% reported by other investigators (20,28,30,31,33,39).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Before insemination, the percentage was 34.3 AE 3.7%. This result was higher than the 3.0% to 22.6% reported by other investigators (20,28,30,31,33,39).…”
Section: Discussioncontrasting
confidence: 63%
“…Other results were controversial and showed a positive relationship between cumulus cell DNA fragmentation and fertilization by ICSI (29), whereas a lack of correlation was found between the incidence of apoptotic cumulus cells and the outcome of ICSI when analyzing only fertilization and embryo quality (30). A negative correlation was reported by Saito et al (24) and Corn et al (31) between embryo quality and apoptotic rates of cumulus cells, with no influence on pregnancy and implantation.…”
mentioning
confidence: 95%
“…This study had sufficient published data to perform a meta-analysis on various types of treatment (IVF, ICSI, and mixed) as well as different type of DNA damage assays (SCSA, TUNEL, Comet, and SCD assays). We obtained a dataset with consistent protocols by excluding four studies with overlapping data38394041 and 18 studies with sperm DNA tests that were not one of the four inclusion tests (SCSA, TUNEL, SCD, or alkaline Comet assay): two studies using neutral Comet assay,4243 two studies using in situ nick translation assay,4445 and 14 studies using slide-based acridine orange staining method.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the fertilization or even pregnancy outcome, after ICSI, does not depend on parameters of semen samples such as concentration, motility, morphology, incidence of spermatozoa with abnormal chromatin condensation, incidence of spermatozoa with DNA fragmentation, or incidence of apoptotic spermatozoa (10)(11)(12)(13)(14)(15)(16)(17). It seems that, in ICSI, the most critical factor for the achievement of fertilization is the oocyte.…”
Section: Discussionmentioning
confidence: 99%